Analisis Stakeholder Dalam Pengembangan Desa Wisata Sangiran - Hendrika Ayuliani Muntiyas; Izza Mafruhah; I Gusti Lanang Putu Tantra (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2024)
The tourism village concept makes tourism development in rural areas a sustainable and community-based sector that can have a widespread impact on the local economy. Sustainable tourism development must pay attention to all stakeholder roles in achieving goals. This research aims to analyze the role of stakeholders in the development of the Sangiran Tourism Village. This research uses the MACTOR (Matrix of Alliance, Tactics Objective and Recommendations) analysis tool. The research results show that there are three main actors in the development of the Sangiran Tourism Village, namely the Krikilan Village Government, Pokdarwis, and the Sangiran Tourism Village Management.